A Study On Evaluating Service Quality Of Mumbai Metro Trains Using Servqual Model - Line 1, Line 2a And Line 7 - Jain, Dr. Aparna; Shah, Ms. Aafreen; Lad, Ms. Kshamata Sachin; Rathod, Ms. Monika (Migration Letters, 2024)
The main aim of the study is to measure the service quality of Mumbai metro trains in general and to evaluate the service quality gap between the perception and expectation of commuters, as there are many metro lines under construction but the present study focuses only on 3 metro lines that are in operation currently, the two new lines of the Mumbai metro viz Line 2A - Andheri West to Anand Nagar and Line 7 - Gundavli to Dahisar started in January 2023 whereas line 1- from Ghatkopar to Versova has operated since 2014. The SERVQUAL Model is used to analyze the service quality gap, 5 constructs of the model were studied consisting of 3 factors in every i.e.15 questions of the SERVQUAL model were used in the study, Data has been collected from 120 Metro travelers of Mumbai City using Google forms. (Minimum sample required at 0.5 effect size, Alpha of 5%, and power of test 95% to apply paired t-test = 54) non-probability convenience sampling technique was used for the current study. Both primary and secondary data collection techniques have been used for the present study. SPSS 26 has been used for the current study, and the technique applied for the analysis is paired t–test. As per the findings of the research, there is no service gap in the constructs of Reliability, Tangibility, and Assurance but there exists a service gap in a few items of empathy and responsiveness.